P083 How do HIV testing initiatives impact on HIV testing rates and diagnosis in primary care?. (8th June 2017) - Rickwood, Lucinda; Perera, Sean; Soni, Suneeta; Dean, Gillian
Abstract : Introduction: Undiagnosed HIV leads to late presentation, increased morbidity, and contributes to onward transmission. It is estimated that in our area approximately 17% of those living with HIV are undiagnosed. Little is known about the impact of National HIV Testing Week (NHTW) initiatives in general practice (GP). In 2016 we implemented a 'pop-up' message alerting GPs that it was NHTW, with a 'one-click' pathway to adding an HIV-test to bloods requested for other reasons. Methods: Number of HIV tests carried out in GP and new HIV diagnoses made were collected between 20 th August 2016 and 20 th February 2017 and separated into the time period spanning 3 months pre-NHTW, NHTW itself and 3 months post-NHTW. Results: 464 HIV tests were performed in 37 GP practices in the pre-NHTW period (approx. 36/week), 96 test during NHTW and 534 tests in 3 month post-NHTW (approx. 41/week). 1 HIV-diagnosis was made in GP during the pre-NHTW period (c.f. 20 across all services), no new diagnoses in NHTW and 1 case (7 across all services) in the 3 month post-NHTW period. Discussion: Testing initiatives result in greater awareness across the city and an increase in HIV testing, which was sustained, although no increase in new HIV diagnoses. The decrease in HIV diagnoses in this study reflects the national trend of a reduction in HIV diagnoses despite increased testing; this is attributed partly to the efficacy and increased use of Pre-exposure prophylaxis (PrEP).